HEART RATE RECOVERY CHANGES FOR HIGH CLASS CANOE SPRINT ATHLETES DURING DIFFERENT TRAINING PERIODS - Veispals, Martins; Gulbe, Antra; Konrads, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
One of the criteria for exercise intensity in sport science is heart rate. Reduced heart rate in exercise indicates heart’s ability to work more effectively. 12 high class flat-water kayakers (Latvian national team members) took part in this study. The main aims of the study were to evaluate the improvements of the heart regeneration rate and the functional condition of the athletes over the time period of 4 years - where all participant repeated a maximum oxygen consumption test on rowing ergometer 43 times (2-6 times per athlete). Heart rate recovery drop was obtained in the first 4 minutes after the maximum oxygen consumption test. For reflection on functional condition, speed on kayak ergometer at lactate concentration in blood values of 1 mmol/l and 3 mmol/l was measured (low-intensity load and submaximal intensity load). Speed on kayak ergometer at a blood lactate value 3 mmol/l show an average increase of 0.96 km/h (By Student’s t – test for related samples and Wilcoxon’s criteria). For heart rate regeneration Wilcoxon’s criterion shows an average increase of 0.46%.